Cyclical fluctuations of iron biomarkers in women: Diagnostic implications for iron deficiency - Aguree, Sixtus; Owora, Arthur; Silveyra, Patricia (Practical laboratory medicine, 2025)
Iron deficiency (ID) and iron deficiency anemia (IDA) are common in women of reproductive age, but the influence of menstrual cycle phase on iron biomarkers is not well defined and is often overlooked in clinical and public health assessments. To assess phase-specific variation in iron biomarkers and the prevalence of ID and IDA in non-pregnant women aged 18–44 years using 2003–2006 NHANES data. We analyzed 1484 women with complete reproductive and iron status data. Menstrual cycle phase was categorized as menstruation (day 1–5), follicular phase (6−15), early/mid luteal phase (16–23), and late luteal phase (24–35). Eight biomarkers were analyzed: serum iron (SI), transferrin saturation (%TS), soluble transferrin receptor (sTfR), ferritin, erythrocyte protoporphyrin (EPP), hemoglobin (Hb), mean corpuscular volume (MCV) and body iron index (BII). ID and IDA were defined using ferritin-, MCV- and BII-based diagnostic models. All statistical models accounted for the complex design of the NHANES survey. SI and %TS were lowest during menstruation and increased across the cycle, peaking in the early/mid-luteal phase (SI: p = 0.001; %TS: p = 0.003). sTfR was highest during menstruation (p < 0.05) compared to other phases, consistent with increased iron requirements. Ferritin, EPP, Hb and MCV remained stable across phases. The prevalence of ID varied by model (10.5 %–22.0 %) but showed no consistent phase differences. In contrast, the prevalence of IDA decreased after menstruation, with composite IDA estimates dropping from 7.5 % during menstruation to 3.7 % in the late luteal phase (p = 0.033). Iron biomarkers and IDA prevalence vary systematically across the menstrual cycle, with iron status being lowest during menstruation and recovering in the luteal phase. Consideration of menstrual phase may improve diagnostic accuracy and interpretation of iron biomarkers in women of reproductive age. •Iron biomarkers (serum iron, transferrin saturation, sTfR) fluctuate significantly across menstrual phases.•Iron deficiency is most frequently detected in the early follicular phase.•Considering menstrual phase may improve diagnostic accuracy for iron deficiency and anemia in reproductive-age women.